BLUE OCEAN STRATEGY PADA USAHA PENGOLAHAN KOPI “UD TYYANA COFFEE” DI KABUPATEN TAPANULI SELATAN - Tanjung, Yulia Windi; Widiasyih, Anugrah Sri (Jurnal AGRISEP, 2021)
Coffee (Coffeea sp.) is an agricultural commodity in the plantation subsector which includes the mainstray export commodity,has high economic value and an important source of foreign exchange (net exporters) for Indonesia. UD Tyyana Coffee is one of the busnisesses that runs agribusiness of coffee commodities ranging from plantations to coffee processing. The aims of this study is to analyze the Blue Ocean Strategy at UD. Tyyana Coffee in the South Tapanuli Regency. This study uses a qualitative descriptive method. The result of the research is in running a large strategic series, UD Tyyana Coffe breaks down strategies that are not yet owned by competitors, such as (1) Improving product quality and HR will provide benefits to consumers by providing maximum results. Creating a trend of locations with cafe nuances and facilities such as homestays will increase the emotional appeal of consumers; (2) In the formulation of the Blue Ocean Strategy, the price offered by UD Tyyana Coffee is very attractive and does not change, so it does not affect consumer purchasing power; (3) The costs incurred for this strategy are still affordable. By improving service, it is only intensified when serving ground coffee to provide education about coffee; (4) Adopting the Blue Ocean Strategy requires commitment and cooperation in its processing.